Knockout of the T-cell receptor and HLA class I genes in human cells using the CRISPR /Cas9 system - Kushniarova, Lizaveta V.; Migas, Alexandr A.; Klych, Hanna V.; Lasiukov, Yauheni A.; Meleshko, Alexander N. (Experimental Biology and Biotechnology, 2022)
The CRISPR /Cas9 system has found a wide application in cell biology as a tool for gene knockout. In particular, the CRISPR /Cas9 system is used to create allogeneic CAR-T lymphocytes by knocking out the genes TRAC, TRBC1, TRBC2 and B2M. To obtain a large number of cells of the desired phenotype, it is necessary to optimise the process of genomic editing, the effectiveness of which is determined by the sgRNA used. In this work, we experimentally determined the most effective sequences that allow to obtain up to 60.3 % of cells negative for the expression of the B2M protein and up to 71.8 % of cells negative for the expression of the T-cell receptor. It has also been shown that the simultaneous use of two sgRNAs for gene knockout demonstrates a lower efficiency compared to using these sgRNAs separately.
Keywords: CRISPR/Cas9; sgRNA; T-cell receptor; B2M; gene knockout